Ionic liquid modified mica nanosheet and preparation method and application thereof

By using supercritical CO2 and ionic liquid to perform high-pressure reactions in mica nanosheet preparation, the complex and leakage problems of existing methods are solved, and efficient and green ionic liquid modified mica nanosheet preparation is achieved, which significantly improves the proton exchange membrane performance.

CN116477636BActive Publication Date: 2024-12-24HUBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310415209.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2024-12-24
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

The existing preparation methods for mica nanosheets are complex, long time, require a variety of chemicals, and require post-treatment to remove polymers or surfactants, which poses a risk of ionic liquid leakage.

Method used

Supercritical CO2 is used as the peeling agent, ethanol as the co-solvent and ionic liquid as the intercalation agent and modifier to prepare mica nanosheets through a high-pressure reactor, and peeling and intercalation are used to utilize the strong permeability and solubility of CO2. Avoid post-processing.

Benefits of technology

The green and efficient preparation of ionic liquid modified mica nanosheets is achieved. The proton exchange membrane has excellent proton conductivity, avoiding the risk of ionic liquid leakage and simplifying the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116477636B_ABST
    Figure CN116477636B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing ionic liquid modified mica nanosheets, using supercritical CO2 as a stripping agent, ethanol as a co-solvent, and ionic liquid as an intercalation agent and a modifier, comprising the following steps: adding mica powder, ionic liquid and ethanol to a high-pressure reactor; after the temperature in the high-pressure reactor reaches a preset value, pumping carbon dioxide into the high-pressure reactor until the gas pressure in the high-pressure reactor reaches a preset value; turning on the stirring device of the reactor, so that the stripping agent, ionic liquid and mica powder are fully mixed and reacted, and the pressure is quickly released after the reaction time reaches a predetermined value; after the gas pressure in the high-pressure reactor drops to normal pressure, centrifuging and collecting the supernatant, and drying to obtain ionic liquid modified mica nanosheets. The method for preparing ionic liquid modified mica nanosheets of the present invention is green and efficient, not only does not require a post-processing process, but also realizes the fixation of ionic liquids to inorganic materials, avoiding the risk of ionic liquid leakage when it is used in electrochemical devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional material preparation, and in particular relates to an ionic liquid modified mica nanosheet and a preparation method and application thereof. Background Art

[0002] Due to the excellent mechanical, optical and electrical properties of ultrathin two-dimensional nanosheets, many layered materials have been successfully exfoliated into single or few layers, such as graphene, hexagonal boron nitride, transition metal dichalcogenides, layered metal oxides, black phosphorus, layered double hydroxides and layered clays (such as montmorillonite). Since the emergence of graphene, the exfoliation of layered materials into two-dimensional nanosheets has attracted widespread attention.

[0003] Mica is a layered clay mineral material with a 2:1 structure. Mica crystals are stacked in two dimensions by an aluminum oxide octahedron layer sandwiched between two identical silicon oxide tetrahedron layers. The Si in the crystal structure is replaced by Al at the tetrahedral position, which makes the mica sheet carry a negative charge. The interlayer is composed of K + Charge balance. Therefore, mica crystals can be peeled along the plane where the positive ions are located, and the ideal plane can be flat at the atomic level. Two-dimensional ultra-thin nanosheets have excellent mechanical, optical and electrical properties, but mica has strong interlayer forces, weak cation exchange capacity, and no expansion, so it is a challenging task to peel mica into single-layer or few-layer nanosheets in large quantities.

[0004] In addition, mica, as a macroscopically transparent natural layered clay, has many excellent properties, including visible light transparency, UV shielding, atomic-level flatness, electrical insulation, temperature stability, and chemical durability. The exfoliated two-dimensional few-layer mica flakes have excellent proton conductivity after proton exchange. At 500°C, the area conductivity of the proton-exchanged single-layer mica can reach 100S cm -2 The above is an excellent proton conductor with broad application prospects in the field of electrolytes. Ionic liquid (IL) is a new type of liquid electrolyte with advantages such as good ionic conductivity, excellent thermal stability, and a wide electrochemical window. It can be widely used in various electrochemical devices, but there is also a risk of ionic liquid leakage. By fixing ionic liquids in inorganic materials to prepare ion gels, ionic liquids can be stably present in the framework without changing their own excellent properties, which is more advantageous in the application of electrochemical devices.

[0005] Patent No. CN110917143A discloses a method for preparing mica two-dimensional nanosheets as drug carriers. The ground mica powder is made into a suspension and then ultrasonicated, and then added to a hydrochloric acid-acidified polypropylene oxide triamine and 2,2-bis-(4-glycolylaminophenyl) propane solution, mechanically stirred at 60-100°C for 2-8h, and centrifuged after removing the polyamine to obtain mica two-dimensional nanosheets. The prepared mica two-dimensional nanosheet drug carrier containing drug ingredients can reduce multidrug resistance and systemic toxicity, and has pH-responsive drug release and selective cytotoxicity. Pan et al. calcined natural mica at 800°C, acidified it with 5 mol / L nitric acid to activate the mica, and then ion-exchanged the activated natural mica with a saturated sodium chloride solution to weaken its interlayer bonding force, and then intercalated the mica after sodium ion exchange with hexadecyltrimethylammonium bromide to expand the interlayer spacing of the mica. Finally, the intercalated mica was ultrasonically treated for 30 minutes and the supernatant was collected after centrifugation at 3000 rpm for 10 minutes to obtain the exfoliated single-layer mica nanosheets. Hyun et al. reacted white mica powder calcined at 750°C with LiNO3 at 300°C for 48 hours, and then used a polymer (PVP)-assisted wet chemical method to exfoliate large-area nanosheets. Amphiphilic polymer molecules were successfully embedded in ion-exchanged white mica particles to separate each layer. The resulting product has nanosheets with micron-scale lateral dimensions, and the thickness of the nanosheets is mainly divided into 1.2-1.7nm and 2.2-2.7nm.

[0006] However, the above preparation methods have complicated preparation processes, take a long time, require the use of a variety of chemicals, and the prepared mica nanosheets often require post-treatment to remove the polymers or surfactants used in the stripping process. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an ionic liquid modified mica nanosheet and its preparation method and application. The present invention uses supercritical CO2 (scCO2) as a stripping agent, ethanol as a co-solvent, and an ionic liquid (IL) as an intercalation agent and a modifier to prepare the ionic liquid modified mica nanosheet, which is green and efficient, not only does not require post-processing and impurity removal, but also realizes the fixation of the ionic liquid to the inorganic material, so that the proton exchange membrane prepared by the ionic liquid modified mica nanosheet prepared by the present invention has excellent proton conductivity.

[0008] To achieve the above object, the present invention is implemented through the following technical solutions:

[0009] The present invention provides a method for preparing ionic liquid modified mica nanosheets, using supercritical CO2 as a stripping agent, ethanol as a co-solvent, and ionic liquid as an intercalation agent and a modifier, comprising the following steps:

[0010] S1. Adding mica powder, ionic liquid and ethanol into a high pressure reactor;

[0011] S2. After the temperature in the autoclave reaches a preset value, carbon dioxide is pumped into the autoclave until the gas pressure in the autoclave reaches a preset value;

[0012] S3. Turn on the stirring device of the reactor so that the stripping agent, ionic liquid and mica powder are fully mixed and reacted. After the reaction time reaches a predetermined value, open the valve to quickly release the pressure;

[0013] S4. After the gas pressure in the high-pressure reactor drops to normal pressure, centrifuge and collect the supernatant, and then dry to obtain the ionic liquid-modified mica nanosheets.

[0014] In step S2 of the present invention, carbon dioxide is pumped into the high-pressure reactor. When the gas pressure in the reactor reaches a preset value, the stirring system is turned on to react. During the reaction, the carbon dioxide is not controlled to circulate, thereby avoiding the risk of the ionic liquid being dissolved in CO2 and then being carried away with the circulating flow.

[0015] Preferably, the ionic liquid in step S1 is an imidazole ionic liquid.

[0016] Preferably, the ionic liquid is [Bmim]Otf, [Bmim][NTf2] or [Bmim]Ac.

[0017] Preferably, in step S1, the usage ratio of mica powder, ionic liquid and ethanol is (0.4-1g): (0.4-1.2g): 6ml.

[0018] Preferably, in step S1, the mica powder is pre-treated before use, and the pre-treatment includes calcination, acidification and salt washing.

[0019] Preferably, the step of pre-treating the mica powder is:

[0020] S1.1. Calcine the mica powder at 750-800°C for 0.5-2h to obtain calcined mica powder;

[0021] S1.2. Add the calcined mica powder to a 3-6 mol / L nitric acid solution, acidify at 70-95°C for 3-6 hours, then filter and wash the filter residue to neutrality to obtain acidified mica powder;

[0022] S1.3. Add the acidified mica powder into a saturated sodium chloride solution, react at 70-95°C for 3-6 hours, then filter and wash until there is no chloride ion in the filtrate to obtain the pre-treated mica powder.

[0023] Preferably, in step S2, the temperature of the autoclave is 40-80° C., and the gas pressure in the autoclave is 7.5-16 MPa.

[0024] Preferably, in step S2, the temperature of the autoclave is 60° C., and the gas pressure in the autoclave is 16 MPa.

[0025] Preferably, in step S3, the magnetic stirring speed of the stirring device is 400 to 800 rpm, and the reaction time is 12 to 24 hours.

[0026] The present invention also provides an ionic liquid modified mica nanosheet prepared by the above preparation method.

[0027] The present invention also provides an application of the ionic liquid modified mica nanosheet prepared by the above preparation method in an electrochemical device, such as preparing a proton exchange membrane.

[0028] The beneficial effects of the present invention are:

[0029] The present invention uses supercritical carbon dioxide to exfoliate mica to prepare mica nanosheets, which is green and efficient. The carbon dioxide overflows naturally after pressure relief without treatment. The added ionic liquid can act as an intercalation agent in the exfoliation process and also as a modifier for the exfoliated mica nanosheets used in electrochemical devices, and also does not need to be removed by post-treatment.

[0030] The present invention utilizes the strong permeability, strong solubility and extremely small surface tension of supercritical carbon dioxide, assisted by shearing action, to achieve the purpose of stripping mica while coating / intercalating mica with ionic liquid to obtain ionic liquid modified mica nanosheets, thereby fixing the ionic liquid on the inorganic material and avoiding the risk of ionic liquid leakage when the mica is used in electrochemical devices.

[0031] The ionic liquid modified mica nanosheet prepared by the invention can significantly improve the proton conductivity of the proton exchange membrane and has broad application prospects in solid electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0033] Figure 1 This is an AFM image of the ionic liquid modified mica nanosheets prepared in Example 1;

[0034] Figure 2 TEM image of the ionic liquid modified mica nanosheets prepared in Example 1;

[0035] Figure 3 This is the EDS image of the ionic liquid modified mica nanosheets prepared in Example 1;

[0036] Figure 4 is the absorbance of the supernatant prepared at different temperatures at 600 nm;

[0037] Figure 5 is the absorbance at 600 nm of the supernatant prepared under different pressures;

[0038] Figure 6 is the absorbance of the supernatant obtained in Example 1 and Comparative Examples 1-2 at 600 nm;

[0039] Figure 7 This is a diagram showing the application effect of the ionic liquid modified mica nanosheets prepared in Example 1 in an electrochemical device. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The embodiment of the present invention provides a method for preparing ionic liquid-modified mica nanosheets, using supercritical CO2 as a stripping agent, ethanol as a co-solvent, and ionic liquid as an intercalation agent and a modifier, comprising the following steps:

[0042] S1. Add mica powder, ionic liquid and ethanol in a ratio of (0.4-1 g): (0.4-1.2 g): 6 ml to a high pressure reactor;

[0043] The mica powder is mica powder obtained by pre-treatment such as calcination, acidification and salt washing, and specifically comprises the following steps:

[0044] S1.1. Calcine 1 to 3 g of mica powder at 750 to 800 ° C for 0.5 to 2 h to obtain calcined mica powder;

[0045] S1.2. Add the calcined mica powder to a 3-6 mol / L nitric acid solution, acidify at 70-95°C for 3-6 hours, then filter and wash the filter residue to neutrality to obtain acidified mica powder;

[0046] S1.3. Add the acidified mica powder into a saturated sodium chloride solution, react at 70-95°C for 3-6 hours, then filter and wash until there is no chloride ion in the filtrate to obtain the pre-treated mica powder.

[0047] S2. After the temperature in the autoclave reaches 40 to 80°C, carbon dioxide is pumped into the autoclave until the gas pressure in the autoclave reaches 7.5 to 16 MPa;

[0048] S3. Turn on the stirring device of the reactor at a stirring speed of 400 to 800 rpm to allow the stripping agent, ionic liquid and mica powder to be fully mixed and reacted. After 12 to 24 hours of reaction, open the valve to quickly release the pressure;

[0049] S4. After the gas pressure in the high-pressure reactor drops to normal pressure, centrifuge and collect the supernatant, and then dry to obtain the ionic liquid-modified mica nanosheets.

[0050] The dosage ratio of mica powder, ionic liquid and ethanol in the embodiment of the present invention is (0.4-1g): (0.4-1.2g): 6ml. For example, in some preferred embodiments, the dosage ratio of mica powder, ionic liquid and ethanol is 0.4g: 0.4g: 6ml, or 1g: 1.2g: 6ml, or 0.5g: 0.6g: 6ml, etc.

[0051] The embodiment of the present invention provides a method for preparing ionic liquid modified mica nanosheets using supercritical carbon dioxide, wherein supercritical carbon dioxide enters between mica layers due to its strong gas-like diffusivity and strong permeability, accompanied by shearing action. During the pressure relief process, the volume expansion of supercritical carbon dioxide expands the mica sheets, thereby achieving the effect of stripping the mica into a few-layer nanosheet. At the same time, ionic liquid is added, and the intercalation or coating of the few-layer mica sheets by the ionic liquid is achieved under the auxiliary effect of supercritical carbon dioxide.

[0052] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] Mica pretreatment: Weigh 3g of mica powder and calcine it at 800℃ for 2h. Then acidify the calcined mica powder in 100mL of 6mol / L nitric acid solution at 95℃ for 5h. After the reaction, filter and wash the residue until it is neutral. Then add the acidified mica powder to 100ml of saturated sodium chloride solution and react at 95℃ for 3h. After the reaction, filter and wash the filtrate to detect whether there is chloride ion.

[0055] Supercritical carbon dioxide treatment: After the pre-treated mica powder is dried, 0.4 g is weighed into a high-pressure reactor, 0.4 g of ionic liquid ([Bmim]Otf) and 6 ml of ethanol are added, carbon dioxide is introduced for 3 minutes to exclude air, and then the temperature is raised to 60°C, and carbon dioxide is introduced again until the pressure in the reactor reaches 16 MPa. The magnetic stirring speed is 400-800 rpm. After reacting for 12 hours, the pressure is quickly released, and the sample is taken out and ethanol is added to 40 mL for dilution. Then, the supernatant is collected by centrifugation at 3000 rpm for 10 minutes. After drying, the supernatant obtains ionic liquid-modified mica nanosheets IL@Mica-scCO2.

[0056] Figure 1 The AFM image of the mica nanosheet prepared in this example is Figure 1 (b) It can be seen that the lateral size of the exfoliated mica is 400nm and the thickness is 1.5nm, which has reached the nanoscale. Figure 2 TEM image of mica nanosheets. Figure 2 (a) It can be seen that the mica has been peeled off into thin flakes. Figure 2 (b) is the separation edge of the mica sheet, showing the ordered atomic structure of mica, indicating the successful exfoliation and high crystallinity of the nanosheet. Figure 3 TEM image and EDS results of mica nanosheets. Al and Si are elements of mica, and N and S are elements of ionic liquid. The results show that the ionic liquid is successfully coated or intercalated into mica.

[0057] Embodiments 2 to 5

[0058] The only difference from Example 1 is that the heating temperature of the autoclave is different, and the rest is the same as Example 1. Specifically, the temperature of the autoclave in Example 2 is 40°C, the temperature of the autoclave in Example 3 is 50°C, the temperature of the autoclave in Example 4 is 70°C, and the temperature of the autoclave in Example 5 is 80°C.

[0059] Embodiments 6 to 9

[0060] The only difference from Example 1 is that the pressure of the high-pressure reactor is different, and the rest is the same as Example 1. Specifically, the pressure of the high-pressure reactor in Example 6 is 7.5 MPa, the pressure of the high-pressure reactor in Example 7 is 10 MPa, the pressure of the high-pressure reactor in Example 8 is 12 MPa, and the pressure of the high-pressure reactor in Example 9 is 14 MPa.

[0061] Comparative Example 1

[0062] The only difference from Example 1 is that the pretreated mica powder is subjected to ordinary heat treatment, specifically: after the pretreated mica powder is dried, 0.4 g is weighed into a reactor, 0.4 g of ionic liquid ([Bmim]Otf) and 6 ml of ethanol are added, the temperature is raised to 60°C, and the magnetic stirring speed is 400-800 rpm. After reacting for 12 hours, the sample is taken out and ethanol is added to 40 mL for dilution, and then centrifuged at 3000 rpm for 10 min to collect the supernatant, and the mica sheet IL@Mica is obtained after drying.

[0063] Comparative Example 2

[0064] The only difference from Example 1 is that the pre-treated mica powder is subjected to supercritical carbon dioxide exfoliation without ionic liquid treatment. Specifically, after the pre-treated mica powder is dried, 0.4 g is weighed in a high-pressure reactor, 6 mL of ethanol is added, carbon dioxide is introduced for 3 minutes to exclude air, and then the temperature is raised to 60°C, and carbon dioxide is introduced until the pressure in the reactor is 16 MPa, the magnetic stirring speed is 400-800 rpm, and the pressure is quickly released after the reaction for 12 hours. After the sample is taken out, ethanol is added to 40 mL for dilution, and then the supernatant is collected at a speed of 3000 rpm for 10 minutes, and the mica sheet Mica-scCO2 is obtained after drying.

[0065] Performance Test:

[0066] The concentration of mica nanosheets obtained by exfoliation varies greatly with the pressure and temperature of supercritical carbon dioxide treatment. Examples 1 to 5 and Examples 6 to 9 respectively explore the effects of temperature and pressure on the ionic liquid-mica system. Take 9 mL of the supernatant obtained by centrifugation of Examples 1 to 9 respectively, and use a UV-visible spectrophotometer to test the absorbance of the dispersion at 600 nm, and use the absorbance to indicate the concentration of mica nanosheets in the supernatant. Figure 4 is the absorbance of mica nanosheets in the supernatant prepared at different temperatures. It can be seen that the concentration of mica nanosheets exfoliated under supercritical carbon dioxide treatment at a temperature of 60°C is the highest; Figure 5 is the absorbance of mica nanosheets in the supernatant prepared under different pressures. It can be seen that the concentration of the exfoliated mica nanosheets increases slowly with the pressure.

[0067] The absorbance test of the supernatant containing mica nanosheets prepared in Example 1, Comparative Example 1 and Comparative Example 2 was performed. The results are as follows: Figure 6 As shown, it can be seen that the concentration of mica nanosheets in comparative example 1 that is not treated with supercritical carbon dioxide is low, and the concentration of mica nanosheets obtained in comparative example 2 that is treated with supercritical carbon dioxide without adding ionic liquid is also low. While the present invention uses supercritical CO2 as a stripping agent to strip mica, ionic liquid as an intercalating agent can achieve intercalation of mica sheets with the assistance of supercritical carbon dioxide, thereby producing mica nanosheets with a higher concentration.

[0068] The ionic liquid modified mica nanosheets prepared in Example 1 of the present invention were used for preparing Nafion composite membranes by casting. Specifically, 0.0225 g (3% content) of ionic liquid modified mica nanosheets were weighed and placed in 3 ml N, N-dimethylformamide (DMF), and dispersed by ultrasonication for 30 min. Then 15 g of 5% Nafion solution (D520) was weighed and poured into the above dispersion, and magnetically stirred at 400 rpm for 24 h. The above solution after uniform dispersion was poured on a culture dish, and the solvent was evaporated by keeping it at 70 ° C for 1 h, 90 ° C for 3 h, and 110 ° C for 1 h on a heating table. The evaporated membrane was peeled off, boiled in 3% hydrogen peroxide solution, deionized water, 0.5% dilute sulfuric acid solution, and deionized water for 1 h, and dried to obtain Nafion-3% IL@Mica-scCO2 proton exchange membrane.

[0069] After the prepared proton exchange membrane was dried, the proton conductivity test was performed at 20% RH. Figure 7 As shown. Figure 7 It can be seen that the proton conductivity of the proton exchange membrane (Nafion-3% IL@Mica-scCO2) with ionic liquid modified mica nanosheets is greatly improved compared with the pure Nafion membrane, indicating that the ionic liquid modified mica nanosheets prepared by the present invention can be used in electrochemical devices and significantly improve the electrochemical performance.

[0070] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0071] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing ionic liquid modified mica nanosheets, characterized in that: Supercritical CO2 is used as a stripping agent, ethanol is used as a co-solvent, and an ionic liquid is used as an intercalation agent and a modifier, and the steps include: S1. The mica powder, ionic liquid and ethanol were added to a high pressure reactor; the ionic liquid is an imidazole ionic liquid; S2. After the temperature in the autoclave reaches a preset value, carbon dioxide is pumped into the autoclave until the gas pressure in the autoclave reaches a preset value; S3. Open the stirring device of the reactor so that the stripping agent, ionic liquid and mica powder are fully mixed and reacted. After the reaction time reaches a predetermined value, open the valve to quickly release the pressure; S4. After the gas pressure in the high-pressure reactor drops to normal pressure, centrifuge and collect the supernatant, and then dry to obtain the ionic liquid-modified mica nanosheets.

2. The method for preparing ionic liquid modified mica nanosheets according to claim 1, characterized in that: The usage ratio of mica powder, ionic liquid and ethanol in step S1 is (0.4 ~ 1 g): (0.4 ~ 1.2 g): 6 ml.

3. The method for preparing ionic liquid modified mica nanosheets according to claim 1, characterized in that: In step S1, the mica powder is pre-treated before use, and the pre-treatment includes calcination, acidification and salt washing.

4. The method for preparing ionic liquid modified mica nanosheets according to claim 3, characterized in that: The steps of pre-treating the mica powder are: S1.

1. Calcine mica powder at 750-800 °C for 0.5-2 h to obtain calcined mica powder; S1.

2. The calcined mica powder is added to a 3-6 mol / L nitric acid solution, acidified at 70-95 °C for 3-6 h, and the residue is washed to neutrality after solid-liquid separation to obtain an acidified mica powder; S1.

3. Add the acidified mica powder into a saturated sodium chloride solution, react at 70-95°C for 3-6 hours, separate the solid and liquid, and wash until there is no chloride ion in the filtrate to obtain the pre-treated mica powder.

5. The method for preparing ionic liquid modified mica nanosheets according to claim 1, characterized in that: In step S2, the temperature of the autoclave is 40-80°C, and the gas pressure in the autoclave is 7.5-16 MPa.

6. The method for preparing ionic liquid modified mica nanosheets according to claim 5, characterized in that: In step S2, the temperature of the autoclave is 60°C, and the gas pressure in the autoclave is 16 MPa.

7. The method for preparing ionic liquid modified mica nanosheets according to claim 1, characterized in that: In step S3, the magnetic stirring speed of the stirring device is 400 to 800 rpm, and the reaction time is 12 to 24 h.